2021
DOI: 10.1111/bjh.17392
|View full text |Cite
|
Sign up to set email alerts
|

Successful tyrosine kinase inhibitor discontinuation outside clinical trials — data from the population‐based Swedish chronic myeloid leukaemia registry

Abstract: Clinical trials show that tyrosine kinase inhibitor (TKI) treatment can be discontinued in selected patients with chronic myeloid leukaemia (CML). Although updated CML guidelines support such procedure in clinical routine, data on TKI stopping outside clinical trials are limited. In this retrospective study utilising the Swedish CML registry, we examined TKI discontinuation in a population-based setting. Out of 584 patients diagnosed with chronic-phase CML (CML-CP) in 2007-2012, 548 had evaluable information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…Another observational study by an Italian research group reported an estimated TFR at 12 months of 69% for patients discontinuing firstand second-line TKI, including 68% for those with imatinib, and 73% for those with second-generation TKI (51). A Swedish group reported that 62.2% of patients discontinuing TKI in clinical practice remained in TFR at the last follow-up (median follow-up time 1.6 years), consistent with the Spanish and Italian studies (52). A single-institution retrospective study also showed that 65% (65/100) patients maintained MR4.5 after a median follow-up of 30 months after discontinuation of TKI.…”
Section: Real-world Tki Discontinuationsupporting
confidence: 66%
“…Another observational study by an Italian research group reported an estimated TFR at 12 months of 69% for patients discontinuing firstand second-line TKI, including 68% for those with imatinib, and 73% for those with second-generation TKI (51). A Swedish group reported that 62.2% of patients discontinuing TKI in clinical practice remained in TFR at the last follow-up (median follow-up time 1.6 years), consistent with the Spanish and Italian studies (52). A single-institution retrospective study also showed that 65% (65/100) patients maintained MR4.5 after a median follow-up of 30 months after discontinuation of TKI.…”
Section: Real-world Tki Discontinuationsupporting
confidence: 66%
“…The estimated TFR was 68.8%, and 65.5% at 12 and 24 months, comparing favorably to the TFR rate of approximately 50% in most clinical studies ( Saussele et al, 2018 ). The rate is also similar to the TFR rate reported in Italian, Spanish, and Swedish patients ( Hernandez-Boluda et al, 2018 ; Fava et al, 2019 ; Flygt et al, 2021 ). After discontinuation, most relapse occurred within the first 6 months.…”
Section: Discussionsupporting
confidence: 87%
“…A study from a Spanish research group described a TFR rate at 4 years of 64% ( Hernandez-Boluda et al, 2018 ). Recently, a Swedish discontinuation study showed that 62.2% of patients maintained TFR at the last follow-up ( Flygt et al, 2021 ). However, limited data are available on TKI discontinuation for Chinese CML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Expert consensus statements and clinical practice guidelines recommend >5 years of imatinib and >3 to 5 years of a 2G-TKI, with a response ≥ MR 4 for ≥2 years [ 2 , 7 9 , 38 , 44 , 46 , 48 , 49 ]. Convincing data supporting these recommendations are lacking [ 10 ].…”
Section: How Many People Can Successfully Discontinue Tki Therapy?mentioning
confidence: 99%
“…Data are from retrospective analyses. Ref Study Initial TKI N Median follow-up (y) Met discontinuation criteria Discontinued Achieved Stable TFR Branford et al [ 22 ] Adelaide IM 400/600/800 423 8 37% NR NR Geelen et al [ 90 ] Dutch IM 400 (75%), 2GTKIs (25%) 382 10 31% 10% NR Flygt et al [ 48 ] Swedish Mainly IM 400 548 9 NR 23% 12% Etienne et al [ 43 ] French Mainly IM 400 398 7 10%–55% 46% 12% Kantarjian et al [ 26 ] ENESTnd IM 400 283 10 30% NR NR Guilhot et al [ 27 ] French SPIRIT IM 400 + LDAC or + IFN α or IM 600 787 13.5 NR 44% 18% Gugliotta et al [ 92 ] GIMEMA NIL 800 73 10 NR 33% 25% Kantarjian et al [ 26 ] ENESTnd NIL 600 282 10 49% NR NR Kantarjian et al [ 26 ] ENESTnd NIL 800 281 10 47% NR …”
Section: How Many People Can Successfully Discontinue Tki Therapy?mentioning
confidence: 99%